PENGARUH LEVERAGE, PROFITABILITAS, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP INCOME SMOOTHING DENGAN MODERASI FIRM SIZE - Shela Thenisia; Agustin Ekadjaja (Jurnal Paradigma Akuntansi, 2026)
The purpose of this study is to empirically examine the influence of leverage, profitability, and institutional ownership on income smoothing practices with firm size as a moderating variable in infrastructure companies listed on the Indonesia Stock Exchange for the 2019-2021 period. There were 40 samples of infrastructure companies that have been selected by purposive sampling technique with a total of 120 data for three years. Data processing used logistic regression analysis with EViews 12 software. The result showed that leverage has a negative influence on income smoothing while profitability and institutional ownership have no influence on income smoothing. Firm size does not moderate leverage and profitability influence on income smoothing practices and strengthens the influence of institutional ownership on income smoothing.